Analisis Alokasi Dana Desa Dalam Pembangunan Infrastruktur Desa (Studi Kasus: Pembangunan Infrastruktur Di Desa Plosokandang) - Chandra Kusuma, Tsakila; Dwi Puspita, Septia; Febriana, Lina; Fajar Riani, Ella; Ti'anatud Diniati, Bintis (widya balina, 2025)
This study aims to analyze the management of Village Fund Allocation (ADD) in infrastructure development in Plosokandang Village, Kedungwaru District, Tulungagung Regency. The focus of the study covers three main stages of ADD management, namely planning, implementation, and evaluation, as well as identifying supporting and inhibiting factors in the realization of development. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the planning stage has implemented participatory principles through the Village Development Planning Deliberation (Musrenbangdes). The community plays an active role in proposing programs, although not all proposals can be realized due to budget limitations. In the implementation stage, infrastructure development proceeds according to the Budget Plan (RAB) and is carried out by the Activity Implementation Team (TPK) with good coordination. Obstacles that arise mainly come from uncertain weather conditions, but can be overcome with technical adjustments. The evaluation stage shows that the entire budget is absorbed 100% without any discrepancy, and all physical activities are achieved according to target. However, community participation in the evaluation is still limited. Supporting factors for success include information transparency, community participation, and accurate priority setting. The main inhibiting factor was the weather, with no administrative or accountability issues identified. Overall, Village Fund Allocation (ADD) management in Plosokandang Village reflects the principles of transparency, accountability, and effective village development.